Improving Business Capacity through Business Management Training - Siahaan, Sabda Dian Nurani (Universitas Negeri Medan, 2024)
The fertilizer business is a business field that will never die because fertilizer is always needed in agriculture. The partner in this proposed service activity is the Suruhen Simpogos Farmers and Livestock Group in Siempat Rube II Village, Siempat Rube District, Pakpak Bharat Regency. This group consists of corn farmers and cattle breeders and is currently transforming into fertilizer entrepreneurs. Along with the increase in cattle farming, a new problem began to emerge, namely the amount of cow manure. With full awareness of environmental conditions, this group processes cow dung into organic fertilizer. However, this fertilizer business has several problems, namely business management is not neat. The solution offered to overcome this problem is to conduct business management training. The method for implementing this activity is training and mentoring. This proposed service activity aims to increase the knowledge and skills of partners in running their business which ultimately leads to increasing business capacity. This activity also aims to support productive businesses based on being environmentally friendly. Handling this problem is urgent because the fertilizer business has great potential to be developed in Pakpak Bharat, where the majority of the population works as farmers.